Does vascular occlusion in liver resections predispose to recurrence of malignancy in the liver remnant due to ischemia/reperfusion injury? A comparative retrospective cohort study. (August 2020) - Theodoraki, Kassiani; Papadoliopoulou, Maria; Petropoulou, Zoe; Theodosopoulos, Theodosios; Vassiliu, Pantelis; Polydorou, Andreas; Xanthakos, Pantelis; Fragulidis, George; Smyrniotis, Vassilios; Arkadopoulos, Nikolaos
Abstract: Background: Severe ischemic changes of the liver remnant after hepatectomy could expedite tumor recurrence on the residual liver. Our study aimed at assessing the effect of warm ischemic/reperfusion (I/R) injuries on surgery-to-local recurrence interval and patient overall survival, during major hepatectomies under inflow and outflow vascular control. Methods: One hundred and eighteen patients were subjected to liver resection under total inflow and outflow vascular clamping and were assigned as study group. These individuals were retrospectively matched to 112 counterparts, who underwent liver surgery applying inflow and outflow vascular clamping only of the segment harboring the tumor, sparing the liver remnant from any I/R injury (control group). The two cohorts were compared regarding recurrence-free survival and overall survival. Results: Reversible I/R injuries of the liver remnant subjected to vascular clamping were manifested, with increase of AST values at postoperative day 2 in the study group, as compared to the control group (603 ± 270 U/L vs. 450 ± 290 U/L, p < 0.001), reversing to normal by day 7. Recurrence-free survival and overall survival were no significantly different between the two groups (log rank statistic p = 0.298 and 0.639, respectively). Conclusion: Reversible I/R injuries of the liver remnant do not seem to be implicated in the precipitation of local malignant recurrence or in shorter long-term survival, in comparison to a technique sparing the residual liver of I/R injury. This retrospective cohort study was registered at clinicaltrials.gov under unique identifying number: NCT04257240. Highlights: Reversible ischemia/reperfusion (I/R) injury of the liver remnant occurs post hepatectomy. I/R injury post hepatectomy is not implicated in the precipitation of local malignant recurrence. I/R injury post hepatectomy does not shorten long term survival. I/R injury post hepatectomy is comparable to a modification of the technique, sparing the residual liver of I/R injury.